An electrochemical studies on alginate-based solid biopolymer electrolytes - Ahmad Salihin, Samsudin; Shamsul, Zakaria; Saifful Kamaluddin, Muzakir (2019)
Solid biopolymer electrolytes (SBE) system which has been accomplished by incorporating various composition of ionic dopant namely ammonium bromide (NH4Br) with alginate using solution casting method. The SBE system shows good physical appearance which clear and transparent. In this research, alginate-NH4Br were characterized using Fourier Transform Spectroscopy (FTIR), X-Ray Diffractometer (XRD) and Electrical Impedance Spectroscopy (EIS). In structural study, there are interaction occur between alginate polymer and NH4Br using FTIR analysis. It shows that the peak start to shift when concentration of NH4Br increased. Besides, the peak intensity also begin to decrease when addition of NH4Br concentration. In advanced, the ionic transport has been studied using Deconvolution technique. It shows that the ionic mobility, μ and diffusion coefficient, D of alginate-NH4Br SBE system is observed to be governed with ionic conductivity. The number of ions mobile, η increase as the concentration of NH4Br also increase. XRD has been used to study the structural of SBE system. The amorphous structure of SBE system start to increase until 20 wt. % and the SBE system shows full crystalline at 30 wt.%. In electrical study, cole-cole plot is used to measure the bulk resistance, Rb of SBE system. Moreover, the ionic conductivity of alginate-NH4Br SBE system is depends on Rb value from cole-cole plot. The lower the Rb value, the highest the ionic conductivity. Meanwhile, the ionic conductivity at room temperature shows increasing value from 4.67 x 10-7 S cm-1 for un-doped sample to optimum value at 4.41 x 10-5 S cm-1 for sample containing with 20 wt. % NH4Br. The SBEs system at higher conductivity shows the lower activation energy, Ea due to formation of ionic cluster at polymer matrix.